M6: A Diploid Potato Inbred Line for Use in Breeding and Genetics Research. Issue 2 (21st February 2014) - Jansky, S. H.; Chung, Y. S.; Kittipadukal, P.
Abstract : M6 (Reg. No. GP‐1, BS 228) is a diploid self‐compatible inbred line of the potato wild relative Solanum chacoense . It is a vigorous, homozygous breeding line derived by self‐pollinating the diploid wild potato relative S. chacoense for seven generations. While most wild Solanum species are self‐incompatible, this clone is homozygous for the dominant self‐incompatibility inhibitor gene Sli . In addition, it is homozygous for 90% of single‐nucleotide polymorphism markers in the Infinium Array developed by the SolCAP consortium. M6 is vigorous and both male and female fertile, producing seeds in crosses to diploid cultivated and wild potato germplasm. These traits enable us to systematically develop diploid inbred lines, which was not possible in potato breeding until the discovery of Sli . M6 produces tubers under both short and long photoperiods, unlike other wild potato relatives. In addition, M6 has several desirable traits, including high dry matter content, good chip processing quality, and resistance to soft rot and Verticillium wilt. M6 is being used to develop recombinant inbred line populations.